Praktik Masyarakat dalam Keberlanjutan Pendidikan Anak di Desa Cigondang, Kecamatan Labuan, Kabupaten Pandeglang (Jurnal ENTITAS SOSIOLOGI, 2023)
Parents need capitals to afford their children's education, especially at tertiary institutions, be it economic capital, social capital, cultural capital and symbolic capital. This study draws from the theory of Pierre Bourdieu's practice by focusing on what capital is owned or used by parents to finance their children's tertiary level education. This study uses a qualitative approach using a case study method. Parents who have the capital to contribute to the continuity of education is a practice carried out by parents, namely social practices related to ways that children can fulfill their life needs, so that parents can meet their children's educational needs and control their child's survival. Every parent who supports financially their child's education up to the tertiary level uses one of the capitals proposed by Bourdieu, namely social capital, economic capital, cultural capital and symbolic capital. However the use of each capital is different in portion/ highlight. Keywords: Pierre Bourdieu, Education Continuity, Cultural Capital, Economic Capital.